China’s Rise and its Implications for Australian Foreign Policy - Petrus K. Farneubun (Cenderawasih University, 2022)
This article places a particular emphasis on the rise of China and its implications for Australian foreign policy. It qualitatively examines the perceptions of China’s rise, its intentions, and the Australian responses, based on government and international organisation reports, and secondary sources such as books, journals, and media articles. Using realism as a theoretical lens, this article argues that Australia’s foreign policy still reflects an ambiguity, as a result of, on the one hand, the economic opportunities China creates, and on the other hand, uncertainty regarding China’s intentions, whether offensive or defensive, peaceful or aggressive. Facing this condition, this article demonstrates that Australia adopts several important policy strategies. First, it maintains a hedging strategy to balance its economic interests and its security concern. Second, Australia continues to rely on the protection of the US. In the long-term, however, this reliance may be changed. For this reason, Australia needs to increase its own military capability. This article concludes that Australian foreign policy will likely remain ambivalent in its response to the rise of China.KEYWORDSAustralia; China’s Rise; Foreign Policy; Military Capability; Power Shift